Noise exposure level detection using the internet of things (IOT) concept - Maja Anachkova, Simona Domazetovska, Petreski Zlatko, Viktor Gavriloski (Forum Acusticum, 2020)
The intense globalization, the steady growth in population and the changes in infrastructure in the last decade have caused multiple negative environmental changes in the large cities. One of the most worrying problems that occurs in overpopulated and frequent urban cities is the problem of increased noise levels which can seriously affect human health. This work presents an environmentally sustainable solution based on an Internet of Things (IoT) platform in the city of Skopje, the capital of North Macedonia for the purpose of 24-hour monitoring of the level of noise in several measuring stations in the city. The final goal of this platform is to serve as a monitoring portal and a credible source for an early warning system of increased noise levels in the city. This paper also focuses on explaining a low-cost sensor design for converting the Units obtained from the monitoring network, into Decibels, as well as the functionality of the sensor network, providing information about the noise exposure situation in the city. In order to predict and perform active measures about the future noise pollution across the city, analysis for the noise levels in 2018 was described and thereafter, conclusions about the most exposed location, month and period of the day are brought. This leads to a better understanding of the dynamics of changes in the noise levels in the city which hasn’t been conducted previously, but at the same time is crucial for further preventing the evident noise pollution enhancement.
Keywords: noise exposure, noise level, IoT, LoRaWAN